Cultural Itineraries in Tuscany - Margherita Azzari (Electronica, 2005)
In the conviction that cultural itineraries must assume a growing importance in a tourism based on the criteria of sustainability, three examples of the valorisation of local culture have been elaborated. This is effectively an important component of sustainable development, one of the fundamental aspects of which is the historic memory of the territory. The growth of the tourist and free time market provides an efficacious stimulus for the development of proposals aimed at prospecting new itineraries and alleviating the more consolidated tourist flows, inserting a vast heritage of landscape and cultural resources within significant territorial fabrics. This is also true from the point of view of growing synergies between economy and culture. The three proposed itineraries unwind through areas of great interest in terms of historical traditions and of specific territorial resources which deserve cultural valorisation, particularly in view of the fact that Tuscany offers an enormous wealth distributed in a capillary manner, but much of which is little known.